Discretization effects on renormalized gauge-field Green's functions, scale setting, and the gluon mass - Boucaud, Philippe; Zafeiropoulos, Savvas (Physical review, 2018)
The SU(3) gauge-field propagators computed from the lattice have been exhaustively used in the investigation of the low-momentum dynamics of QCD, in a judicious interplay with results from other nonperturbative approaches, and for the extraction of fundamental parameters of QCD like Λ MS as well. The impact of the discretization artifacts and their role in the extrapolation of the results to the continuum limit have not been fully understood so far. We report here about a very careful analysis of the physical scaling violation of the Landau-gauge propagators renormalized in the momentum subtraction scheme and the Taylor coupling, steering us towards an insightful understanding of the effects from discretization artifacts which makes therefore possible a reliable continuum-limit extrapolation.